Age-related reductions in arousal-enhanced memory are moderated by trait emotion regulation - Kyoungeun Lee; Brialisse Sayre; Taylor A. James; Audrey Duarte (Scientific Reports, 2023)
Abstract Emotional arousal is known to enhance episodic memory in young adults. However, compared to valence, little is known about how healthy aging impacts arousal-enhanced memory effects. Furthermore, while emotion regulation is believed to improve with age, it is unclear how individual differences in emotion regulation influence arousal-enhanced memory. In this large-scale online study, we investigated the impact of age and individual differences in emotion regulation on arousal-enhanced memory. During encoding, participants made arousal ratings about negative, neutral, and positive images, and we compared their subsequent memory of high and low-arousal images. We found the impact of emotional arousal on memory was reduced with age, especially for older adults who habitually suppress their emotions. Our findings show that arousal-related memory benefits are reduced with advancing age, and that individual differences in habitual usage of emotion regulation impact these age-related alterations.